Hodgkin Lymphoma Mimicking Inflammatory Breast Carcinoma: A Rare Case with Diagnostic Challenge and Novel Treatment - Eleni Thodou; Maria Befani; George Triantafyllidis; Theodosia Choreftaki; George Kanellis; Nikolaos Giannakoulas (Case Reports in Hematology)
Extranodal Hodgkin lymphoma involving the breast is infrequent. Most cases reported in the literature were diagnosed by histology after lumpectomy. We present a Hodgkin lymphoma mimicking inflammatory breast carcinoma in a 57-year-old woman. The diagnosis was performed by fine-needle aspiration (FNA) of the breast lesion and the axillary lymph nodes with rapid on-site evaluation followed by immunocytochemistry, and it was confirmed by histology. The patient after first-line chemotherapy developed relapse/refractory disease. Salvage chemotherapy regimens were applied with poor results and severe toxicity. Total remission was achieved with monotherapy of brentuximab vedotin, a novel anti-CD30-targeted antibody drug conjugate. This is a unique case of breast HL with misleading clinical presentation initially diagnosed by cytology. FNA as a minimally invasive diagnostic tool was crucial in avoiding unnecessary breast surgery and further delay of chemotherapy. It is also the first report highlighting the importance of this novel immunotherapy in the management of refractory Hodgkin lymphoma with breast involvement.